SOME FEATURES OF NEOPATRIMONIAL POLITICAL COMMUNICATIONS - Авксентьєв, О. Л. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2020)
The article emphasizes the concept of neopatrimonial political regimes for specific features highlighting of political communications in third world countries since on the Afro-Asian material the traditional science-theoretical division into democratic, authoritarian and totalitarian regimes is not effective enough. Behind the formal signs of democratic regimes in many countries of the world, including in the countries of the former Soviet Union, lies the patrimonial logic of their functioning. The characteristic features of neopatrimonial regimes are distinguished: the “gap” between the center and the periphery, the construction of socio-political relations according to the patronage-client scheme, the dominant role of the state in the political system, “privatization” of state functions by representatives of the state-bureaucratic complex, turning them into a source of private income.It is noted that under this conditions in the political-communicative subsystem of the political system the specific model of power-oligarchic space is formed, within which presence of own media channels, the ability to control and censor information flows acquires on a special role. This contributes to the deployment of lobbying and corruption networks, which are becoming an integral mechanism for the functioning of neopatrimonial regimes. The problem of the peculiarity of the lexis in neopatrimonial communications is considered, namely, the widespread use of the so-called invective or obscene vocabulary. It is suggested that it is not caused by low educational or general cultural level of individual political actors, but by the tendency of cultivation the informal aspect of political communications inherent in neopatrimonial regimes. The question is posed that for further research on the specifics of neopatrimonial communications, one of the most promising approaches is the identification of the main models of neopatrimonial regimes and analysis of the features of their development.